2020
DOI: 10.1039/d0tc02366c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced carrier separation in ferroelectric In2Se3/MoS2 van der Waals heterostructure

Abstract: Enhanced carrier separation in ferroelectric In2Se3/MoS2 van der Waals heterostructure and external electric field effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…As In 2 Se 3 has different structural phases, we only study the most stable reported 19 phase, namely α-In 2 Se 3 . α-In 2 Se 3 belongs to the R3m space group with a hexagonal crystal structure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As In 2 Se 3 has different structural phases, we only study the most stable reported 19 phase, namely α-In 2 Se 3 . α-In 2 Se 3 belongs to the R3m space group with a hexagonal crystal structure.…”
Section: Methodsmentioning
confidence: 99%
“…The optimized lattice parameter of α-In 2 Se 3 is 4.10 Å which agrees with the previously reported values. 19 FGT possesses a hexagonal crystal structure. Each layer is composed of five sublayers with a sandwich-like stacking sequence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This amount of charge transfer is also within the range of previous studies (10 −1 –10 −3 e ). [ 34,37–41 ] The charge accumulation leads to an alteration in the built‐in electric field from the g‐C 3 N 4 monolayer to the α‐In 2 Se 3 monolayer. According to the parallel‐plate capacitor model described in Equation (4), the alteration of the built‐in electric field is of the order of 4.0 × 10 −3 V Å −1 (for configurations A/B).…”
Section: Resultsmentioning
confidence: 99%